ANALYSIS OF FARMER DECISI IN DETERMINING MONOCULTURE AND INTERCROPPING SYSTEM IN PAKONG VILLAGE PAKONG DISTRICT PAMEKASAN REGANCY - Edi Sunandar Riyadi; Yanti Nurmalasari; Sustiyana Sustiyana (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2021)
This study aims to determine the condition of agriculture in Pakong Village Pakong District Pamekasan Regency and to determine the decision makking Factors of farmer and determining monokulture and intercropping system. The location of the research was carrid out intentionally in Pakong Village Pakong District Pamekasan Regency. The sampel method useed in this study is a deliberate method and to find out the number of samples the researches here use the slovin formula. Data analysis techniques are carrid out by means of qualitative descriptions and percentage description. The results showed that agriculture in Pakong Village has increased from year to year both in terms of land use and plant selection. And farmers' decision making in choosing a monoculture cropping system is 54.0% more than intercropping, on the grounds that it is easier to maintain and easy to irrigate, it has even become a habit for farmers to apply monoculture planting systems, there are also farmers who have side jobs.